The Lessons of History - Durant, Will, 1885-1981 and Durant, Ariel (New York Simon and Schuster, 1987)
Includes material on the influence of biology, race, character, morals, religion, economics, socialism, government, and war on history.
Includes Notes and Index.
Keywords: History -- Philosophy